The intention of undergraduate accounting students in Universiti Teknologi Malaysia to pursue profesional accounting qualification - Zharith Sofhia Mohamad Ahad, 1996-, author; Kamaruzzaman Abdul Rahim, supervisor; Sekolah Perniagaan Antarabangsa Azman Hashim (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Perakaunan) - Universiti Teknologi Malaysia, 2018